PEMIKIRAN TOKOH-TOKOH PENDIDIKAN INDONESIA, KONTRIBUSI SERTA IMPLIKASI DALAM PENDIDIKAN - Yakob Godlif Malatuny (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2016)
Education is one of the human development index of Indonesia, certainly requires analysis and philosophical thinking to formulate the fundamental purpose and deep. Writing aims to examine the thinking of education in Indonesia and contributions as well as the implications in the world of education. Philosophically, the thoughts of a character education Indonesia was influenced by the ideology of Pancasila. In addition, historical background and religion also affect the flow of thought the character of education.